Naturism Stigma Scale: Adaptation of a Standardised Measure of Stigma Towards Naturism - Kerem Kemal Soylemez; Joanne Lusher; Marina Rachitskiy (Psychology International)
Background: Stigma can have a significant impact on the lives of those inflicted, and stigmatisation can occur at any time when individuals commonly label behaviours and characteristics of others as offensive. Many attributes, such as homosexuality, ethnicity, race, and mental illness, have been explored using existing instruments. However, there are currently no standardised measures of stigma towards specific behaviours such as naturism. Naturism is the practice of public nudity without any intention of sexual stimulation. Though a global phenomenon, data suggest that almost seven million individuals in the UK alone identify as naturists. The rising figures of those engaging in stigmatised behaviour and the negative representations of this in the media contribute to the necessity for standardised instruments to measure stigma towards naturism. Method: The Naturism Stigma Scale (NSS) was adapted from the Depression Stigma Scale. This 18-item scale has two subscales which measure personal and perceived stigma. The sample consisted of 449 participants recruited by convenience sampling. Results: The analysis indicated that the scale had high reliability for both subscales (Personal Cronbach’s α = 0.91, Perceived Cronbach’s α = 0.93). It can be concluded that the NSS is a reliable psychometric instrument. Conclusions: Overall, this research assists in further understanding the stigma towards this minority group. Further research is necessary to explore the psychometric properties of NSS among different community samples.